STUDENTS’ DIFFICULTIES IN READING COMPREHENSION IN RELATION TO THEIR LEARNING STYLE - Amrullah, Sitti Zakiyah; Weda, Sukardi; La Sunra, La Sunra (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study aims to find out what problems students often face when they learn to understand what they read, what makes these problems happen, and how these problems differ based on how students like to learn. It looked at students in class XI.A at SMA Insan Cendekia Syech Yusuf. The study used a questionnaire called The VARK 8.0, and interviews. The results showed that students usually struggle with long the text is, the student's interest, how the teacher explains things, the student's background, physical problems, technical problems, and not having enough time. In the interviews, students talked about how their learning style affects their reading problems. For example, visual learners struggle with long texts, auditory learners have trouble with vocabulary, read/write learners find it hard to finish in time, and kinesthetic learners have issues with vocabulary and pronouncing words. Overall, the biggest problems for all learning styles were related to vocabulary and pronunciation.